Technological factors towards student’s achievement in mathematics - Mohd Nasir, Farah Damia; Ghazali, Norliza; Hussain, Al Mahdi; Mohammed, Harnani; Arshad, Adli (Macrothink Institute, 2022)
The purpose of this study is to investigate the relationship between the technological factors on student learning that affect the result in Mathematics subject. The findings in this study are based on the questionnaire and test distributed among students in SMK Lembah Subang. The research used random sampling of 60 Form 4 students in SMK Lembah Subang. Data were collected through close-ended and open-ended questions using a Likert scale. The pre-test and post-test were conducted to measure students’ performance. Respondents were represented from various classes (four classes). The data were then analysed using SPSS software. The result has shown that educator’s skills and environment have a significant impact toward students’ performance in SMK Lembah Subang. The finding showed that technology application has no significant relationship with students’ performance.